2016
DOI: 10.5194/cp-2016-21
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Summer-temperature evolution on the Kamchatka Peninsula, Russian Far East, during the past 20,000 years

Abstract: Abstract. Little is known about the climate evolution on the Kamchatka Peninsula during the last deglaciation as existing climate records do not reach beyond 12 ka BP. In this study, a summer-temperature record for the past 20 ka is presented. Branched Glycerol Dialkyl Glycerol Tetraethers, terrigenous biomarkers suitable for continental air temperature reconstructions, were analyzed in a sediment core from the western continental margin off Kamchatka/marginal Northwest Pacific (NW Pacific). The record reveals… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 96 publications
1
5
0
Order By: Relevance
“…Therefore, Barr and Clark (2011) considered the first scenario unlikely. In light of our findings, and with evidence for warm gLGM summers being widespread in Siberia (Alfimov and Berman, 2001;Elias, 2001;Kienast et al, 2005;Sher et al, 2005;Berman et al, 2011;Meyer et al, 2016 a), the relatively high precipitation estimates may now appear more likely. As such, and despite the ambiguity in the Pekulney Mountains, the DDM-derived precipitation estimates for the three mountain ranges (the Sredinny, Kankaren and Pekulney) emphasize that summer temperature may have been an important limiting factor for glacier growth in the Pacific Sector of Siberia at the gLGM.…”
Section: Implications For Glacier Growth In Ne Russia At the Glgmsupporting
confidence: 58%
“…Therefore, Barr and Clark (2011) considered the first scenario unlikely. In light of our findings, and with evidence for warm gLGM summers being widespread in Siberia (Alfimov and Berman, 2001;Elias, 2001;Kienast et al, 2005;Sher et al, 2005;Berman et al, 2011;Meyer et al, 2016 a), the relatively high precipitation estimates may now appear more likely. As such, and despite the ambiguity in the Pekulney Mountains, the DDM-derived precipitation estimates for the three mountain ranges (the Sredinny, Kankaren and Pekulney) emphasize that summer temperature may have been an important limiting factor for glacier growth in the Pacific Sector of Siberia at the gLGM.…”
Section: Implications For Glacier Growth In Ne Russia At the Glgmsupporting
confidence: 58%
“…This isolation is thought to have been located in northeastern Siberia or on the now submerged Bering Sea shelf, lasting between 7000 and 15,000 years (36) during what is known as the "Beringian standstill." Some terrestrial records support the interpretation that this region was an ecological refugium, with spruce, birch, and alder pollen and fossil insects providing evidence of a relatively mild and maritime climate (37). However, given the extremely cold conditions further inland (38), it has remained unclear how habitable conditions could have been maintained.…”
Section: Regional Warming In Beringia Due To Enhanced Pmocmentioning
confidence: 87%
“…However, the problem with this assumption is that the western edge of mountain glaciers on the Kamchatka Peninsula is almost 1500 m above the sea level. In addition, Meyer et al (2016) reported that MAT-derived summer SST in east Kamchatka during the Last Glacial Maximum (LGM) was as high as present. If so, then the extent of sea ice in the east Kamchatka Peninsula was limited at this time.…”
Section: Cause Of Provenance Changes In the Okhotsk Seamentioning
confidence: 99%